The Molecular Epidemiology of Cystic and Alveolar Echino-coccosis Disease in Southeast Turkey - Fadime Eroglu; Mehmet Dokur; Yuksel Ulu (Iranian Journal of Parasitology, 2021)
Background: The migration of humans and climatic and environmental changes cause the emergence of infectious diseases. This study aimed to investigate the changes in the molecular epidemiology of the Echinococcosis disease in the southeast region of Turkey after migrations.